2021
DOI: 10.1007/s12144-021-02480-2
|View full text |Cite
|
Sign up to set email alerts
|

Do students with immigrant and native parents perceive themselves as equally engaged in school during adolescence?

Abstract: Student engagement in school needs to be considered when comparing immigrant and native students, particularly at a time of increasing migratory movements throughout the world. Differences in cognitive, affective, behavioral, and agentic student engagement dimensions were examined for students with immigrant and native parents, and for early and middle adolescence. A four-dimensional measure of student engagement was completed by 643 students (52.7% women). Results indicated that: students with native parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 88 publications
3
24
0
3
Order By: Relevance
“…Risk neighborhoods are those communities with greater poverty, delinquency, unemployment, violence, or drug use, in comparison to middle-class neighborhoods [ 1 , 2 , 3 ]. Parents’ main responsibility is raising children [ 4 , 5 ]. However, opportunities for child and adolescent healthy development could be lower in risk neighborhoods than in middle-class neighborhoods [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Risk neighborhoods are those communities with greater poverty, delinquency, unemployment, violence, or drug use, in comparison to middle-class neighborhoods [ 1 , 2 , 3 ]. Parents’ main responsibility is raising children [ 4 , 5 ]. However, opportunities for child and adolescent healthy development could be lower in risk neighborhoods than in middle-class neighborhoods [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the scale dimensions developed by prior research have varied in structure based on diverse understandings of the concept of student learning engagement. For example, some studies have found that student engagement scales containing four dimensions of cognitive, affective, behavioral, and agentic dimensions are effective in countries such as Portugal and Iran [ 72 , 73 ]. However, due to the difference in social contexts and cultural traditions, we gave preference to scales that had been tested in previous studies and were widely used.…”
Section: Methodsmentioning
confidence: 99%
“…An a priori power analysis ( Faul et al, 2009 ) was estimated that a minimum of 448 participants was needed to conduct the study with a medium-small effect-size with a high power (α = 0.05, 1–β = 0.95; d = 0.35) in a univariate t -test with two groups ( Garcia Perez et al, 1999 ; Garcia et al, 2008 ; Veiga et al, 2021 ). Present study sampling the self-concept of 36–72-month-old children attending preschool education in public and private preschools in one large city with a total of 54,346 preschool children in Turkey and in one medium-sized city with 10,775 preschool children in Germany.…”
Section: Methodsmentioning
confidence: 99%